2013
DOI: 10.4995/wrs.2013.1236
|View full text |Cite
|
Sign up to set email alerts
|

Resources allocation in reproductive rabbit does: a review of feeding and genetic strategies for suitable performance

Abstract: This article reviews how frequent feeding and selection programmes can affect resource allocation in rabbit does during reproduction. The consequences of these programmes and the central role of body condition for suitable female performance are analysed considering genetic level, health and welfare. Future reproductive potential of reproductive rabbit females is decided before first partum. There is enough evidence of a possible threshold for the rabbit female birth weight to reach the beginning of reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 111 publications
(150 reference statements)
4
44
0
1
Order By: Relevance
“…On the other, the mean weights at AI were lower for primiparous and multiparous does in group I (4307 vs. 4516 and 4514 g and 4461 vs. 4698 and 4782 g, respectively, in groups S and E). These results are in agreement with those of Pascual et al (2013), who showed that the total body energy of rabbit does increases from the 1 st AI to the 4 th AI (34.8 vs. 59.4 MJ, Figure 1b). Parigi-Bini and Xiccato (1993) observed large energy losses (28%) by primiparous does during lactation due to largely simultaneous requirements for lactation, body growth and pregnancy.…”
Section: Weight and Body Composition Of Doessupporting
confidence: 82%
“…On the other, the mean weights at AI were lower for primiparous and multiparous does in group I (4307 vs. 4516 and 4514 g and 4461 vs. 4698 and 4782 g, respectively, in groups S and E). These results are in agreement with those of Pascual et al (2013), who showed that the total body energy of rabbit does increases from the 1 st AI to the 4 th AI (34.8 vs. 59.4 MJ, Figure 1b). Parigi-Bini and Xiccato (1993) observed large energy losses (28%) by primiparous does during lactation due to largely simultaneous requirements for lactation, body growth and pregnancy.…”
Section: Weight and Body Composition Of Doessupporting
confidence: 82%
“…In this sense, LP females presented higher intake and reduced milk production compared to L females. We argue that LP females split the acquired resources between the current and the next litter, as described by Fortun-Lamothe et al (1999) and cited by Pascual et al (2013) and Savietto et al (2015). At this point the priority is the future litter, as the current one is able to compensate the lower milk yield by eating, a strategy that does not compromise offspring survival.…”
Section: Discussionmentioning
confidence: 99%
“…nutritional composition), and their reproductive effort (i.e. size of the litter being raised and the interval between consecutive reproductive cycles) are recognised factors that affect their nutritional status (Fortun-Lamothe, 2006;Pascual et al, 2013;Savietto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the productivity of rabbit farms has increased but, at the same time, several problems related to the health status and the welfare of does also have appeared, for example excessive replacement rates, high mortality and culling rates and hypo-fertility (Rosell and de la Fuente, 2009;Sánchez et al, 2012). In addition, the nutritional requirements of the animals have had to be revised according with the new physiological demands (Xiccato, 1996;Pascual et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A considerable degree of body fat mobilization before parturition was also reported by Brecchia et al (2006) and Arias-Alvarez et al (2009) which observed that the blood concentration of NEFA reached the highest concentration at parturition in comparison to the first month of lactation. Pascual et al (2013) hypothesized that this response is a result of the large degree of foetal growth during late pregnancy (almost doubled in the last 3 days; Mocé et al, 2004), while the maternal body experiences to intense catabolism (Parigi-Bini et al, 1990). Moreover, the negative energy balance condition at the end of gestation could be worsened by the decrease of feed intake around the parturition (Xiccato, 1996) which induces hypoinsulinaemia in does (Brecchia et al, 2006), preventing the use of glucose as energy source and consequently the increase of lipid catabolism and NEFA concentrations (Rebollar et al, 2011).…”
Section: Effect Of Transition Period In Reproductive Rabbit Doesmentioning
confidence: 99%